Global and Regional Cardiovascular Mortality Attributable to Nonoptimal Temperatures Over Time - Hundessa, Samuel; Huang, Wenzhong; Zhao, Qi; Wu, Yao; Wen, Bo; Alahmad, Barrak; Armstrong, Ben; Gasparrini, Antonio; Sera, Francesco; Tong, Shilu; Madureira, Joana; Kyselý, Jan; et al. (Journal of the American College of Cardiology, 2024)
BACKGROUND: The association between nonoptimal temperatures and cardiovascular mortality risk is recognized. However, a comprehensive global assessment of this burden is lacking. OBJECTIVES: The goal of this study was to assess global cardiovascular mortality burden attributable to nonoptimal temperatures and investigate spatiotemporal trends. METHODS: Using daily cardiovascular deaths and temperature data from 32 countries, a 3-stage analytical approach was applied. First, location-specific temperature-mortality associations were estimated, considering nonlinearity and delayed effects. Second, a multivariate meta-regression model was developed between location-specific effect estimates and 5 meta-predictors. Third, cardiovascular deaths associated with nonoptimal, cold, and hot temperatures for each global grid (55 km × 55 km resolution) were estimated, and temporal trends from 2000 to 2019 were explored. RESULTS: Globally, 1,801,513 (95% empirical CI: 1,526,632-2,202,831) annual cardiovascular deaths were associated with nonoptimal temperatures, constituting 8.86% (95% empirical CI: 7.51%-12.32%) of total cardiovascular mortality corresponding to 26 deaths per 100,000 population. Cold-related deaths accounted for 8.20% (95% empirical CI: 6.74%-11.57%), whereas heat-related deaths accounted for 0.66% (95% empirical CI: 0.49%-0.98%). The mortality burden varied significantly across regions, with the highest excess mortality rates observed in Central Asia and Eastern Europe. From 2000 to 2019, cold-related excess death ratios decreased, while heat-related ratios increased, resulting in an overall decline in temperature-related deaths. Southeastern Asia, Sub-Saharan Africa, and Oceania observed the greatest reduction, while Southern Asia experienced an increase. The Americas and several regions in Asia and Europe displayed fluctuating temporal patterns. CONCLUSIONS: Nonoptimal temperatures substantially contribute to cardiovascular mortality, with heterogeneous spatiotemporal patterns. Effective mitigation and adaptation strategies are crucial, especially given the increasing heat-related cardiovascular deaths amid climate change.
Keywords: cardiovascular death; nízká teplota; kardiovaskulární nemoci; Cardiovascular Diseases; Global Burden of Disease; nonoptimal temperatures; celosvětové zdraví; Humans; lidé; excess death; Global Health; death ratio; Cold Temperature